Body size, maturation and motor performance in young soccer players: relationship to technical actions in small-sided games - da Costa, Julio Cesar; Borges, Paulo Henrique; Ramos-Silva, Luiz Fernando; Muller Reis Weber, Vinicius; Moreira, Alexandre; Vaz Ronque, Enio Ricardo (Biology of Sport, 2023)
The objective of this study was to investigate the relative contributions of body size, skeletal age, and motor performance variables with technical actions through an ecological model during small-sided soccer games, and the interaction of biological maturation with technical and motor performance in young players. In this cross-sectional study, eighty-two young players (14.4 ±1.1 years), belonging to state-level soccer teams and divided by category (U-13 and U-15), were included. Players having an injury in the evaluation period were not included in the study. Measurements of body size, skeletal age (SA), motor tests, and technical actions in small-sided games (SSG) were performed (3×3 plus goalkeeper) in two periods (halves) of four minutes. Differences between age groups were found for SA (ES = -2.36), chronological age (ES = -3.89), body mass (ES = -2.09), height (ES = -1.90), and fat-free mass (ES = -2.09). Positive associations were found between body size (R = 0.43 to R = 0.48) and manipulation (R = 0.50 to R = 0.52) indicators and numbers of technical actions (CB and SS), except for stature with LB (R = -0.42) in the U-13 age group. In the U-15 category, skeletal age (R = -0.29 to R = -0.30) and body mass (R = -0.28 to R = -0.29) were negatively associated with the number of technical actions (RB, NB, LB, and OB) (P > 0.05) and positively with the balance with LB (R = 0.26). In conclusion, body size, SA, and motor performance influenced technical actions in SSG differentially in each category. U-13 heavier players and those with a better motor performance presented higher involvement due to the higher number of performed technical actions (receiving the ball, playing a neutral and playing an offensive ball) during SSG.